Cavernous carotid artery large aneurysm treated with a new flow diverter – Xcalibur aneurysm occlusion device (AOD). Issue 5 (October 2020) - Chauhan, Richa Singh; Kathrani, Nihar Vijay; Kulanthaivelu, Karthik; Prasad, Chandrajit; Gupta, Arun Kumar
We report a case of an unruptured, symptomatic, large right cavernous internal carotid artery aneurysm successfully treated with a new balloon-expandable flow diverter – Xcalibur Aneurysm Occlusion Device (AOD). Follow up imaging performed at six months demonstrated complete exclusion of the aneurysm and regression in dimensions, resulting in resolution of mass effect and clinical improvement.